2021
DOI: 10.1161/atvbaha.121.316203
|View full text |Cite
|
Sign up to set email alerts
|

Response by Mackman et al to Letter Regarding Article, “Patients With COVID-19 Have Elevated Levels of Circulating Extracellular Vesicle Tissue Factor Activity That Is Associated With Severity and Mortality—Brief Report”

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…We do not add substantial advancing in the debate concerning whether it is better to measure levels of TF activity or TF protein as marker of thrombotic risk, [ 23 , 24 ] however we clearly show that the TF protein level on the surface of EV consistently predict the severity of COVID-19 disease. We have also shown that CD142-bearing EVs have an augmented enzymatic activity when isolated from serum of patients with severe disease and a poor prognosis, regardless the method of isolation.…”
Section: Discussionmentioning
confidence: 63%
“…We do not add substantial advancing in the debate concerning whether it is better to measure levels of TF activity or TF protein as marker of thrombotic risk, [ 23 , 24 ] however we clearly show that the TF protein level on the surface of EV consistently predict the severity of COVID-19 disease. We have also shown that CD142-bearing EVs have an augmented enzymatic activity when isolated from serum of patients with severe disease and a poor prognosis, regardless the method of isolation.…”
Section: Discussionmentioning
confidence: 63%
“…We did not investigate other possible origins of TF + EVs (i.e., platelets) which may account for this finding. It is worth mentioning that there is some controversy surrounding the use of flow cytometry for TF + EVs detection, since the suggested method to measure TF + MVs is EV-associated TF activity ( Nieuwland et al, 2019 ; Mackman et al, 2021 ). Rosell A. et al reported that EV-TF activity was significantly higher in patients with COVID-19 vs. healthy controls ( Rosell et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although some investigators have used flow cytometry to determine the cellular origin of circulating TF-positive EVs, we feel that this technique is not sensitive enough to simultaneously measure levels of cell typespecific markers and TF on EVs because of the low levels of TF. 69 We speculate that a likely source of circulating TF-positive EVs is activated monocytes because these cells have been shown to express it is possible that other cell types, such as endothelial cells, neutrophils, and epithelial cells, also release TF-positive EVs into the circulation in COVID-19 patients.…”
Section: Sars-cov-2mentioning
confidence: 90%
“…At present, we do not know the cellular origins of the TF‐positive EVs present in the circulation of COVID‐19 patients. Although some investigators have used flow cytometry to determine the cellular origin of circulating TF‐positive EVs, we feel that this technique is not sensitive enough to simultaneously measure levels of cell type‐specific markers and TF on EVs because of the low levels of TF 69 . We speculate that a likely source of circulating TF‐positive EVs is activated monocytes because these cells have been shown to express TF in COVID‐19 patients.…”
Section: Tf Expression and Coronavirusesmentioning
confidence: 96%